Renal Denervation Therapy (RDT) in Resistant Hypertension (BIRDEM Medical Journal, 2012)
Resistant hypertension is defined as blood pressure that remains above therapeutic goal despite the use of three antihypertensive drugs including a diuretic. As much as one third of patients with arterial hypertension are treatmentrefractory as they do not reach sufficient blood pressure control despite combination antihypertensive therapy of significant duration. The hyperactivity of sympathetic nervous system (SNS) in the occurrence of treatment-resistant long standing hypertension has been established both in animal models and in clinical practice. In these patients, the kidneys play a central role as an activator of the sympathetic nervous system. The failure of purely pharmacological approaches to treat resistant hypertension has stimulated interest in invasive device-based treatments based on old concepts. In the absence of orally active antihypertensive agents, patients with severe and complicated hypertension were widely treated by surgical denervation of the kidneys until the 1960s, but this approach was associated with a high incidence of severe adverse events and a high mortality rate. A new catheter system using radiofrequency energy has been developed, allowing an endovascular approach to renal denervation and providing patients, with resistant hypertension, with a new therapeutic option that is minimally invasive and can be performed rapidly under local anaesthesia. With this method the afferent and efferent sympathetic nervous fibers surrounding the renal artery are ablated precisely keeping the renal artery intact. To date, this technique has been evaluated only in open-label trials including small numbers of highly selected resistant hypertensive patients with suitable renal artery anatomy. The available evidence suggests a significant and persistent blood pressure-lowering effect and a very low incidence of short & long term complications with no deleterious effects on renal function. These data, although promising, need confirmation in larger randomized controlled clinical trials with longerterm follow-up.DOI: http://dx.doi.org/10.3329/birdem.v2i2.12325(Birdem Med J 2012; 2(2): 104-112)